Associations between statin use and progression in men with prostate cancer treated with primary androgen deprivation therapy. (2nd November 2017) - Mikkelsen, Marta Kramer; Thomsen, Frederik Birkebæk; Berg, Kasper Drimer; Jarden, Mary; Larsen, Signe Benzon; Hansen, Rikke Bølling; Brasso, Klaus
Abstract: Introduction: In several observational studies, statin use has been associated with reduced risk of progression and mortality in men with prostate cancer (PCa). The study aim was to investigate the association between statin use at time of PCa diagnosis and time to PCa progression in men with advanced or metastatic PCa receiving androgen deprivation therapy (ADT) as primary treatment. Patients and methods: The study population consisted of all men receiving ADT as primary therapy at two Danish Urological Departments in 2007–2013. The primary outcome was time to progression defined as castration-resistant PCa (CRPC) or PCa death. Survival analyses were conducted with Kaplan-Meier analyses, cause specific Cox proportional hazards models, and competing risk analyses. Results: A total of 537 men were included, of whom 141 were statin users at time of diagnosis. The median follow-up time was 5.7 years (95% CI: 5.1–6.2). No significant difference in progression-free survival between statin users and non-statin users was observed at 5 years; 29% for statin users (95% CI: 19–40%) and 28% (95% CI: 23–34%) for non-statin users, p  = 0.31. In multivariable Cox analyses, there was no significant association between statin use and risk of progression, HR 0.98 (95% CI: 0.72–1.32). In competing risk analyses the 5-year cumulative incidence of progression was 55% (95% CI: 46–64%) for statin users and 62% (95% CI: 57–67%) for non-statin users, p  = 0.11. Conclusion: In the current study, statin use at time of PCa diagnosis was unrelated to time to progression in men primarily treated with ADT.